Persepsi pemustaka terhadap layanan perpustakaan “Rumah Ilmu” Universitas Negeri Semarang - Mokhamad Zakaria Eko Handoyo; Muhamad Burhanudin; Amalia Rahmadhani (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. Universitas Negeri Semarang (UNNES) Main Library is committed to providing excellent services. One of the activities is to understand the users’ needs. This paper investigates the users’ perceptions of UNNES Main Library services. The objectives of the study include; (1) determining users’ perception on library services quality, (2) Examining satisfaction level of library services, (3) Measuring users’satisfaction level based on Service Satisfaction Index. Data Collection Methods. The paper used a quantitative methods approach with questionnaires, involving 203 library users, selected randomly. Data Analysis. The data were descriptively analysed by using an online survey tool (SurveyGizmo.com). Results and Discussion. The results report; (1) Users were satisfied with library services quality, but less satisfied with book collections; (2) Satisfaction level of library services was satisfactory; (3) Average score of customer satisfaction was 2.89, within the interval scale of 2.52 to 3.27. Conclusions. Based on the findings concluded that user’s perceptions of UNNES library services were satisfied and furthermore, the UNNES library will continue to improve the quality of services until it achieves very satisfying results.